Forms of the Bajo language register in the coastal community of Bajo Village, Tilamuta District - Malabar, Sayama; Ntelu, Asna; Djou , Dakia N.; Lantowa, Jafar (BAHASTRA, 2026)
This study examines the forms of language registers in the Bajo language as used by the coastal community of Bajo Village, Tilamuta District. While previous studies have primarily focused on language attitudes and contact phenomena, this research addresses a critical gap by analyzing how registers operate as domain-specific systems of meaning that organize knowledge, social roles, and everyday practices. Using a qualitative descriptive approach, data were collected through observation and elicitation of naturally occurring utterances across three key domains: fishing, trade, and education. The findings reveal that Bajo registers extend beyond lexical variation and function as structured semiotic systems embedded in social life. In the fishing domain, registers encode ecological knowledge, procedural labor, and maritime cognition through stable lexical items and morphologically marked verbs. In the trading domain, registers construct economic roles, transactional processes, and material classifications, reflecting both market-based and reciprocal forms of exchange. In the educational domain, registers emerge within a context of institutional bilingualism, where Bajo mediates the transmission of formal knowledge, supports classroom interaction, and localizes educational practices. This study argues that Bajo registers function simultaneously as communicative tools, cognitive frameworks, and cultural archives. Their continued use across multiple domains demonstrates that linguistic vitality is sustained not only through attitudes but through the functional integration of language in economic and institutional practices. By foregrounding the epistemic and social dimensions of register, this study contributes to sociolinguistic scholarship on language maintenance in multilingual coastal communities.